The Influence of Marketing Mix on Customer Decisions in BSI KCP Wonogiri - Steviana Lesti Arvianti; Meilana Widyaningsih (Universitas Islam Negeri Alauddin Makassar, 2025)
This study aims to analyze the influence of the marketing mix (7Ps), which includes product, price, place, promotion, people, physical evidence, and process, on the decision to become a customer at Bank Syariah Indonesia (BSI) KCP Wonogiri. This research uses a quantitative approach with a descriptive method. The population consists of BSI KCP Wonogiri customers, with a sample of 145 respondents selected through a probability sampling technique. Data were collected using questionnaires and analyzed through validity, reliability, classical assumption tests, multiple linear regression, t-test, F-test, and coefficient of determination (R²) using SPSS software. The results show that simultaneously, the marketing mix variables significantly influence the decision to become a customer. Partially, the variables of price, place, and process have a significant effect, while product, promotion, people, and physical evidence do not. These findings suggest that affordable pricing, convenient location access, and efficient service processes are the main factors influencing customers’ decisions to join BSI KCP Wonogiri